Higher Dietary Inflammatory Index scores are associated with brain MRI markers of brain aging: Results from the Framingham Heart Study Offspring cohort. Issue 2 (6th May 2022) - Melo Van Lent, Debora; Gokingco, Hannah; Short, Meghan I.; Yuan, Changzheng; Jacques, Paul F.; Romero, José R.; DeCarli, Charles S.; Beiser, Alexa S.; Seshadri, Sudha; Himali, Jayandra J.; Jacob, Mini E.
Abstract: Introduction: We investigated cross‐sectional associations between the Dietary Inflammatory Index (DII) and measures of brain volume and cerebral small vessel disease among participants of the Framingham Heart Study Offspring cohort. Methods: A total of 1897 participants (mean ± standard deviation, age 62±9) completed Food Frequency Questionnaires and brain magnetic resonance imaging (MRI). Results: Higher (pro‐inflammatory) DII scores, averaged across a maximum of three time points, were associated with smaller total brain volume (beta ± standard error: –0.16 ± 0.03; P < .0001) after adjustment for demographic, clinical, and lifestyle covariates. In addition, higher DII scores were associated with smaller total gray matter volume (–0.08 ± 0.03; P = .003) and larger lateral ventricular volume (0.04 ± 0.02; P = .03). No associations were observed with other brain MRI measures. Discussion: Our findings showed associations between higher DII scores and global brain MRI measures. As we are one of the first groups to report on the associations between higher DII scores and brain volume, replication is needed to confirm our findings.